2006
DOI: 10.1016/j.juro.2006.03.071
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of FK1706 on Erectile Function Following Bilateral Cavernous Nerve Crush Injury in a Rat Model

Abstract: Bilateral cavernous nerve crush causes reproducible erectile dysfunction, consistent with prior experiments. High dose subcutaneous FK1706 therapy promotes significant neuroregeneration and erectile function recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 19 publications
4
35
1
Order By: Relevance
“…10,57 Recently, a crush injury model has been used to mimic nerve-sparing radical prostatectomy. 7,9 In this study, we combined nerve crush with cryo-injury because we aimed to create a severe nerve injury model, which preserves the neural sheath, but takes a considerable time to achieve nerve regeneration, similar to the clinical outcomes observed in patients receiving nerve-sparing radical prostatectomy, and confirmed that nerve regeneration hardly occur for at least 4 weeks after the nerve injury using our methods.…”
Section: Discussionsupporting
confidence: 59%
“…10,57 Recently, a crush injury model has been used to mimic nerve-sparing radical prostatectomy. 7,9 In this study, we combined nerve crush with cryo-injury because we aimed to create a severe nerve injury model, which preserves the neural sheath, but takes a considerable time to achieve nerve regeneration, similar to the clinical outcomes observed in patients receiving nerve-sparing radical prostatectomy, and confirmed that nerve regeneration hardly occur for at least 4 weeks after the nerve injury using our methods.…”
Section: Discussionsupporting
confidence: 59%
“…1) became available as tool compounds and were extensively tested in a variety of animal models such as sciatic [6,7,9,10], cavernous [11,12] or optic nerve crush [13], spinal cord injury [14][15][16], streptozotocin-induced diabetic neuropathy [17,18], or MPTP-or 6-OHDA-induced degeneration of dopaminergic neurons (Table 1) [19][20][21]. These studies provided enticing indications that non-immunosuppressive FK506 analogs might be useful for the treatment of various forms of physical nerve injury, painful diabetic neuropathy or Parkinson's disease.…”
Section: The Rise and Fall Of The Neuroimmunophilin Conceptmentioning
confidence: 99%
“…Alternative evidences suggest the neuromodulatory actions might course through an anti-apoptotic effect, protecting neurons by the upregulation of glutathione (antioxidant) and production of neurotrophic factors. Interestingly, the fact that IPLs mainly target injured nerves and molecular signaling for FK1706 and GPI1046 likely involves immunophilin type-specific binding proteins, damaged neurons should expressed those specific binding proteins, as reported for FK506 [29,96,97].…”
Section: Role Of Immunophilins In the Treatment Of Neurogenic Erectilmentioning
confidence: 75%
“…It is believed that FK1706 have a FKBP12-independent action, thus subsequently causing calcineurin inhibition and the disruption of the cytokine synthesis cascade [96,97]. Alternative evidences suggest the neuromodulatory actions might course through an anti-apoptotic effect, protecting neurons by the upregulation of glutathione (antioxidant) and production of neurotrophic factors.…”
Section: Role Of Immunophilins In the Treatment Of Neurogenic Erectilmentioning
confidence: 99%